Kecenderungan Cinderella Complex pada wanita : Bagaimana peranan pola asuh permissive indulgent? - Wijaya, Stefanie; Noviekayati, IGAA; Ananta, Aliffia (INNER: Journal of Psychological Research, 2023)
This study aims to determine the correlation between permissive indulgent parenting style and cinderella complex tendencies in female students. This research is a type of quantitative research using correlational research. The subjects of this study were 96 female students at the University of 17 August 1945 Surabaya. The data collection method was carried out through distributing questionnaires online using a Google form using a Likert scale. The data analysis technique obtained in this study showed that there was a fairly strong unidirectional relationship between permissive indulgent parenting and cinderella complex tendencies with a correlation score of 0.338. That is, there is a fairly strong positive relationship between the two variables so that the greater the permissive indulgent parenting style given, the greater the individual’s tendency to experience cinderella complex.